Effects of C$H2 and CH on Strength and Hydration of Calcium Sulphoaluminate Cement Prepared from Phosphogypsum - Jixin Zhang; Jun Chang; Ping Zhang; Tong Wang (Buildings, 2022)
Using phosphogypsum (PG) as a raw material to prepare calcium sulphoaluminate cement (CAS) is an effective way of treating phosphogypsum. In order to meet the different application requirements of CSA cement and promote the application of CAS cement, it is necessary to add mineral admixtures to adjust the performance of cement. This paper incorporated two minerals, gypsum dihydrate (C$H2) and calcium hydroxide (CH), into cement clinker prepared from phosphogypsum. The compressive strength and hydration process of the mixtures with different blending levels were investigated around the C4A3$-C$H2 system (SC) and the C4A3$-C$H2-CH system (SCC). The optimum dosing level was determined on the basis of the strength and hydration properties. In the SC system, adding C$H2 promoted the hydration of C4A3$. The compressive strength of the cement was highest at a C$H2/C4A3$ molar ratio of 1.5, with a 7-day compressive strength of 56.5 MPa. AFt was mostly needle-rod and columnar and was tightly cemented to the gel phase, improving the denseness of the matrix. When the molar ratio was 2, the strength of the cement was inverted, and the shape of the AFt changed from needle and rod to columnar, the size of the grains increased, and it could not be filled with the AH3 phase in an excellent staggered manner. At the same time, C$H2 was not fully reacted, increasing matrix porosity and inversion of strength. In the SCC system, adding CH reduced the cement’s compressive strength, and the compressive strength reduction increased with the increase in admixture. According to the experimental results, CH inhibited the formation of AFt, resulting in the appearance of new hydration products, AFm. As the amount of CH increased, the amount of hydration products, AFm, increased, while the amount of AFt and AH3 decreased. However, adding CH raised the paste’s pH and later facilitated the development of strength. The optimum admixture of CH/C4A3$ was 0.5 mol.